Prosedur Pembentukan Peraturan Desa - Yeheskel Wessy; Stelvia W. Noya; Micael Ririhena (FUNDAMENTUM : Jurnal Pengabdian Multidisiplin, 2025)
This community service activity aims to enhance the understanding and capacity of the Village Governments and Village Consultative Bodies (BPD) of Wonreli, Abusur, Lebelau, and Oirata in the process of formulating Village Regulations (Peraturan Desa or Perdes) that are aligned with legal principles and applicable statutory provisions. The socialization was motivated by the generally low level of understanding regarding both the procedures and substance of Perdes formulation, which has led to weak regulatory quality at the village level. The methods employed in this activity included lectures, interactive discussions, and simulations of Perdes drafting, all of which referred to Law Number 12 of 2011 on the Formation of Legislation. The results of the activity indicated a significant increase in legal awareness and participants’ understanding of the importance of legality, participation, and transparency in the village legislative process. This activity also succeeded in encouraging local initiatives to formulate village regulations that are more responsive, accountable, and tailored to the real needs of the local community. Therefore, this socialization made a tangible contribution to strengthening democratic and law-based village governance.